State behaviour and dynamics of self-propelled Brownian squares: a simulation study. Issue 19 (15th April 2016) - Prymidis, Vasileios; Samin, Sela; Filion, Laura
Abstract : We study the state behaviour of self-propelled and Brownian squares as a function of the magnitude of self-propulsion and density using Brownian dynamics simulations. Abstract : We study the state behaviour of self-propelled and Brownian squares as a function of the magnitude of self-propulsion and density using Brownian dynamics simulations. We find that the system undergoes a transition from a fluid state to phase coexistence with increased self-propulsion and density. Close to the transition we find oscillations of the system between a fluid state and phase coexistence that are caused by the accumulation of forces in the dense phase. Finally, we study the coarsening regime of the system and find super-diffusive behaviour.